Registration of 'LCS Wizard' Wheat. Issue 1 (21st October 2015) - Liu, L.; Barnett, M. D.; Griffey, C. A.; Malla, S.; Brooks, W. S.; Seago, J. E.; Butler, H.; Thomason, W. E.; Rucker, E. G.; Behl, H. D.; Pitman, R. M.; Dunaway, D. W.; et al.
Abstract : The objective of this research was to develop widely adapted hard winter wheat ( Triticum aestivum L.) varieties to meet the needs of mills, bakeries, and consumers in the eastern and Great Plains regions of the United States. 'LCS Wizard' (Reg. No. CV‐1111, PI 669574), a hard red winter (HRW) wheat, was developed and tested as VA08HRW‐80 and co‐released by the Virginia Agricultural Experiment Station and Limagrain Cereal Seeds, LLC in 2013. LCS Wizard was derived from the three‐way cross S.6742/92PAN1#33//92PIN#107 using a modified bulk breeding method. LCS Wizard is a widely adapted, high‐yielding, awned, semidwarf ( Rht1 ) HRW wheat with midseason spike emergence and resistance or moderate resistance to diseases prevalent in the mid‐Atlantic and Great Plains regions. In the 2014 Uniform Bread Wheat Trial conducted over 17 locations in eastern states, LCS Wizard produced an average grain yield of 4717 kg ha −1, similar to 'Vision 45' (4650 kg ha −1 ). In the northern Great Plains, the average grain yield over 54 locations in 2012 of LCS Wizard (4419 kg ha −1 ) was slightly lower than that of 'Overland' (4659 kg ha −1 ). In the southern Great Plains, its average grain yield (3844 kg ha −1 ) over 85 locations was slightly higher than that of Fuller (3757 kg ha −1 ). LCS Wizard has acceptable end‐use quality in both the eastern and Great Plains regions of the United States.